Competitive Advantage As A Mediation Factor That Influences The Sustainability Of Halal SMEs - Nanang Apriliyanto (LPPM ISNJ Bengkalis, 2023)
In the first quarter of 2022, only ten percent of Indonesia's food and beverage industry has received halal certification. This small percentage means this research aims to support SMEs by investigating the influence of halal certification, entrepreneurial orientation, gaining competitive advantage, and adopting business sustainability. This research is a quantitative type of explanatory research with a population of 485 SMEs in the food and beverage sector in Kendal regency. Meanwhile, the sample used purposive sampling and obtained 200 respondents from SME owners. Structural equation modelling (SEM) is used with the Smart-PLS test tool as an analysis technique. This research's findings show a positive and significant influence between halal certification and entrepreneurial orientation on competitive advantage and business sustainability. Apart from that, competitive advantage positively and significantly influences business sustainability. Competitive advantage can directly mediate the influence between entrepreneurial orientation and halal certification on business sustainability, which shows a positive and significant direction. This research makes a significant academic contribution by investigating the relationship between halal certification, entrepreneurial orientation, and competitive advantage in SME sustainability.